2021
DOI: 10.1016/j.ergon.2021.103136
|View full text |Cite
|
Sign up to set email alerts
|

Perturbation effect of noise on overall feeling of discomfort from vertical whole-body vibration in vibro-acoustic environment

Abstract: The human discomfort from combined noise and vibration has been investigated with a new perspective. The concept in perturbation effect has been adopted to formulate a new novel predictive model of human discomfort from noise and vibration. A psycho-physics experiment has been designed to identify the perturbation effect which caused by noise stimulus. The experiment involved twelve (12) subjects. Each subject was imposed in random order with a total of 42 combinations of seven (7) levels of noise (X, 61, 71, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The participants rated their discomfort relative to reference stimuli after exposure to each combination. The findings unveiled a predictive equation for discomfort caused by vibration [2].…”
Section: Flywheel: Jurnal Teknik Mesin Untirtamentioning
confidence: 90%
See 1 more Smart Citation
“…The participants rated their discomfort relative to reference stimuli after exposure to each combination. The findings unveiled a predictive equation for discomfort caused by vibration [2].…”
Section: Flywheel: Jurnal Teknik Mesin Untirtamentioning
confidence: 90%
“…Investigating perturbations and their impact on vibration dynamics and control has garnered substantial attention [1][2][3][4][5]. This study delves into the relationship between perturbations and mechanical failure, aiming to unravel novel insights into this complex interplay.…”
Section: Introductionmentioning
confidence: 99%
“…The work of submariners requires alternating day and night, which is physically demanding. Previous studies have pointed out that alternating day and night shifts require full consideration of human adaptability, with night and day shifts needing to be at least 48 h apart when they cross over 41 . The results of this study could provide insights into the development of the submersible field.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies have confirmed that noise can change the perception of vibration. Aladdin et al [25], for example, described a perturbation effect from noise to vibration and, based on this, modeled a prediction equation for the total annoyance of random whole-body vibration under the influence of noise. The authors assumed that from the equivalence point of noise and vibration, the noise has a synergetic effect on the total annoyance and, below that, an antagonistic effect.…”
Section: Prediction Of Relative Total Annoyance With Multiple Linear ...mentioning
confidence: 99%